Diet supplementation with phytase and xylanase on laying performance, egg quality, apparent metabolizable energy, and phosphorous use in laying hens - Autchara Kayan; Sombat Prasongsook; Theerawit Poeikhampha (Veterinary World)
Background and Aim: The inclusion of supplementary enzymes, such as phytase and xylanase, in poultry diets enhances nutrient digestibility and reduces excreta output, minimizing environmental impact. This study aimed to evaluate the effects of phytase and xylanase supplementation on laying performance, egg quality, apparent metabolizable energy (AME), and phosphorus utilization in laying hens.